Determination of the 31P and 207Pb Chemical Shift Tensors in Pyromorphite, Pb5(PO4)3Cl, by Single‐Crystal NMR Measurements and DFT Calculations. Issue 21 (7th November 2017) - Zeman, Otto E. O.; Moudrakovski, Igor L.; Hoch, Constantin; Hochleitner, Rupert; Schmahl, Wolfgang W.; Karaghiosoff, Konstantin; Bräuniger, Thomas
Abstract : The chemical shift (CS) tensors for 31 P and 207 Pb in the natural mineral pyromorphite, Pb5 (PO4 )3 Cl, were determined from orientation‐dependent NMR spectra of a single crystal, and MAS‐NMR spectroscopic experiments. For the two crystallographically independent lead atoms in the hexagonal crystal lattice with space group P 63 / m, the NMR parameters derived from the tensor eigenvalues are δ iso = –2172 ppm, η cs = 0.08 for the 207 Pb at Wyckoff position 6 h, and δ iso = –2810 ppm, η cs = 0.49 for position 4 f . For the 31 P, which are also located at positions 6 h, δ iso = –1.74 ppm and η cs = 0.21 was found. A multi‐parameter fit was utilized to extract the tensors from spectra acquired with one crystal rotation axis. The fit was sufficiently overdetermined to also include the orientation of the crystal rotation axis into the fit, which could not be determined by X‐ray diffraction because of the high absorption coefficient of pyromorphite, caused by the large lead content, and the large crystal size. In contrast to the precisely determined tensor eigenvalues, the orientation of the eigenvectors in the crystal ab‐plane of the pyromorphite system could only be resolved by using the results of density functional theory (DFT) calculations. Abstract :